Environmental transformations a geography of the anthropocene - Whitehead, Mark 1975- (Routledge, 2014)
"From the depths of the oceans to the highest reaches of the atmosphere, the human impact on the environment is significant and undeniable. These forms of global and local environmental change collectively signal the arrival of a new geological epoch: the Anthropocene. This is a geological era defined not by natural environmental fluctuations or meteorite impacts, but by collective actions of humanity. Environmental Transformations offers a concise and accessible introduction to the human practices and systems that sustain the Anthropocene. It combines accounts of the carbon cycle, global heat balances, entropy, hydrology, forest ecology, and pedology, with theories of demography, war, industrial capitalism, urban development, state theory, and behavioural psychology. This book charts the particular role of geography and geographers in studying environmental change and its human drivers. It provides a review of critical theories that can help to uncover the socio-economic and political factors that influence environmental change. It also explores key issues in contemporary environmental studies, such as resource use, water scarcity, climate change, industrial pollution and deforestation" -- Provided by publisher.